Adventitious shoot growth in Grammatophylum scriptum var. Leopard Blume under colchicine and oryzalin applications - Dwiati Murni; Hery Susanto Agus (BIO Web of Conferences)
Grammatophylum scriptum var. Leopard Blume is of great demand due to its uniqueness flowers showing tiger-like patterns in color. This can still be developed further to make it the main element of a cut flower arrangement. Polyploidization offers the potentials of producing better plant vigour and performance in comparison to its diploid counterparts. This study aims to investigate the effectiveness of colchicine and oryzalin in inducing polyploidization in G. scriptum var. Leopard and to determine the most optimum concentration of the substances in producing desired polyploid G. scriptum var. Leopard. An experiment method was arranged in a Completely Randomized Design employing eight treatments consisting of four colchicine concentrations and four oryzalin concentrations. Some morpho-anatomical characters were used as the parameters to examine. Plants under both colchicine and oryzalin showed fresh green in colour. Even sturdier and larger size were observed in the oryzalin-treated plants. Stomata and epidermal cells enlarged leading to a decrease in stomata number and density. It can be concluded that oryzalin of 75 μM was found to be the most optimum treatment as it produced plants of wide and sturdy leaves supported by numerous roots and higher plant habitus.